Spinal Cord Injured (SCI) patients Length of Stay (LOS) prediction based on admission data - Mazhar, Tabib Ibne; Suha, Nusrat Jahan (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.